Prevalence and its risk factors of diabetic patients in urban area of Palakkad: an observational study - M., Ameesh; S., Murugan (International Journal Of Community Medicine And Public Health, 2017)
Background: Diabetes mellitus (DM) is emerging as a major health-care challenge for India. The worldwide prevalence of DM has risen dramatically in the developing countries over the past two decades. Most studies from western countries and urban studies of India point out that lifestyle changes, sedentary life, diet and related epidemiological transition as major risk factors in the development of DM. Methods: It was a cross sectional observational study done in urban area covered under urban primary health Centre (UPHC) of Govt. Medical College, Palakkad. Adults more than 30 years of age in urban area were included and observation period was from 2016-2017. Results: The overall prevalence of diabetes mellitus in the present study was found to be 268 (65.68%). In this 135 (50.37%) were the age group is 50-59 years and almost half 80 (29.85%) were diagnosed at the age of 40-49 years. Similarly, the risk factors such as age, occupation, diet, smoking, alcohol, truncal obesity and family history were significantly associated with prevalence of T2DM whereas alcohol and hypertension were not. Conclusions: The result of the present study proves that prevalence of T2DM was influenced by many risk factors like age, diet, dyslipidaemia, truncal obesity and family history consider more important in the urban studies.